Coencapsulation of alendronate and doxorubicin in pegylated liposomes: a novel formulation for chemoimmunotherapy of cancer. (20th October 2016) - Shmeeda, Hilary; Amitay, Yasmine; Gorin, Jenny; Tzemach, Dina; Mak, Lidia; Stern, Stephan T.; Barenholz, Yechezkel; Gabizon, Alberto
Abstract: We developed a pegylated liposome formulation of a dissociable salt of a nitrogen-containing bisphosphonate, alendronate (Ald), coencapsulated with the anthracycline, doxorubicin (Dox), a commonly used chemotherapeutic agent. Liposome-encapsulated ammonium Ald generates a gradient driving Dox into liposomes, forming a salt that holds both drugs in the liposome water phase. The resulting formulation (PLAD) allows for a high-loading efficiency of Dox, comparable to that of clinically approved pegylated liposomal doxorubicin sulfate (PLD) and is very stable in plasma stability assays. Cytotoxicity tests indicate greater potency for PLAD compared to PLD. This appears to be related to a synergistic effect of the coencapsulated Ald and Dox. PLAD and PLD differed in in vitro monocyte-induced IL-1β release (greater for PLAD) and complement activation (greater for PLD). A molar ratio Ald/Dox of ∼1:1 seems to provide an optimal compromise between loading efficiency of Dox, circulation time and in vivo toxicity of PLAD. In mice, the circulation half-life and tumor uptake of PLAD were comparable to PLD. In the M109R and 4T1 tumor models in immunocompetent mice, PLAD was superior to PLD in the growth inhibition of subcutaneous tumor implants. This new formulation appears to be a promising tool to exploit the antitumor effects of aminobisphosphonates in synergy with chemotherapy.